Instructional influences on English language learners' storytelling. (June 2017) - Ma, Shufeng; Anderson, Richard C.; Lin, Tzu-Jung; Zhang, Jie; Morris, Joshua A.; Nguyen-Jahiel, Kim; Miller, Brian W.; Jadallah, May; Scott, Theresa; Sun, Jingjing; Grabow, Kay; Latawiec, Beata M.; et al.
Abstract: The goal of this study was to evaluate instructional influences on the storytelling of English Language Learners (ELLs). Participants were 210 fifth-grade Spanish-speaking ELLs (mean age = 10.8) from schools serving low-income neighborhoods in the Midwest of the United States. They received a six-week socio-scientific unit involving collaborative group work or direct instruction, or were in control classes that continued regular instruction. In an essay to evaluate mastery of the instructional unit, students from collaborative groups produced significantly longer chains of reasoning (more chains with 5–8 links) than direct instruction students (more chains with 3 or 4 links), while control students were unable to display any extended reasoning. Following the unit, students individually told a story prompted by a wordless picture book to evaluate their oral English proficiency. The stories were coded for several features of basic language production, story completeness, and multi-link causal reasoning. The results indicated that students who received the socio-scientific unit told stories with more complicated syntax than the control students, while no difference in complexity of syntax was observed between students from the two instructional conditions. Stories told by students who had participated in collaborative groups contained significantly more elaboration of essential story elements than the stories produced by direct instruction students or control students. Students who had interacted in collaborative groups also generated significantly longer chains of reasoning (many 5–7 link chains) connecting story events than students in the other two conditions (mostly 1 or 2 link chains). The results suggest collaborative group work may be an effective instructional approach to foster ELLs' communicative competence and causal reasoning. Highlights: Collaborative group work improved English language learners' ability to tell coherent stories. Students from collaborative groups told stories that contained more elaboration of essential story elements. Students from collaborative groups generated longer causal chains that connected story elements.